2004
DOI: 10.1002/pssa.200406852
|View full text |Cite
|
Sign up to set email alerts
|

Growth ofβ-FeSi2 single crystals by the chemical vapor transport method

Abstract: In order to grow β‐FeSi2 single crystals by the chemical vapor transport (CVT) method, the growth conditions, including density of iodine transport agent and growth duration, were examined. An iodine density of 8.9 mg cm–3 was thought to be optimum in the present experiment. It was found that the growth duration should be over 4 weeks for growing β‐FeSi2 single crystals. X‐ray structural analysis revealed that the growth direction of the β‐FeSi2 crystals was The growth rate along the directions with lower Mill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[22][23][24] Previous investigation results have suggested that if I 2 was introduced into the solvothermal system, the synthesis temperature of preparing nanomaterials could also be greatly reduced. For example, metastable rocksalt phase GaN was prepared via a benzene-thermal metathesis route through the reaction of GaI 3 and NaNH 2 at 210 C, in which I 2 acted as the transport agent.…”
Section: Introductionmentioning
confidence: 98%
“…[22][23][24] Previous investigation results have suggested that if I 2 was introduced into the solvothermal system, the synthesis temperature of preparing nanomaterials could also be greatly reduced. For example, metastable rocksalt phase GaN was prepared via a benzene-thermal metathesis route through the reaction of GaI 3 and NaNH 2 at 210 C, in which I 2 acted as the transport agent.…”
Section: Introductionmentioning
confidence: 98%